B2B customer journeys: Conceptualization and an integrative framework - Purmonen Arttu; Jaakkola Elina; Terho Harri (Elsevier, 2025)
Marketing practitioners and consultants have widely adopted the concept of customer journeys for use in analyzing contemporary B2B customer behavior, but despite this concept's potential, research on B2B customer journeys remains in its infancy. This study conceptualizes the B2B customer journey by synthesizing research on customer journeys, B2B purchase processes and buying centers, and business relationships. The study contributes to the extant research by explicating the conceptual underpinnings and core elements of the B2B customer journey, as well as by providing a novel, customer-centric definition of the concept. The developed conceptual framework for B2B customer journeys connects the concept with goal-oriented buying and usage center members, placing equal importance on the purchase and usage stages of the journey and acknowledging its iterative nature and embeddedness in relationships. Thus, the conceptualization offers a comprehensive, up-to-date perspective on B2B customer behavior that is applicable in diverse areas of B2B marketing, such as customer experience management, digital marketing, sales, service management, and service design.